2017
DOI: 10.1159/000471845
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Fragmented QRS in Patients with Hypertrophic Cardiomyopathy

Abstract: Objectives: The relationship between a fragmented QRS (fQRS) and clinical outcomes in patients with hypertrophic cardiomyopathy (HCM) remains unclear.This study aimed to investigate the prognostic significance of fQRS in patients with HCM. Methods: Between 2000 and 2012, 326 unrelated patients with HCM (72% male with a mean age of 52 years) were included and were divided into 2 groups: those with fQRS and those without fQRS. Results: A total of 105/326(32.2%) patients with HCM presented with fQRS at enrollment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 19 publications
0
22
0
1
Order By: Relevance
“…Identifying those who would benefit from an ICD is challenging but The importance of fQRS, which is suggestive of myocardial scarring and fibrosis, has been increasingly supported by recent studies of MAE in various cardiac diseases (Das et al, 2006;Konno et al, 2015;Lu et al, 2017;Sha et al, 2011;Take & Morita, 2012), including HCM (Debonnaire et al, 2015;Konno et al, 2015;Lu et al, 2017). Fibrosis or tissue heterogeneity increases susceptibility to reentry and arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Identifying those who would benefit from an ICD is challenging but The importance of fQRS, which is suggestive of myocardial scarring and fibrosis, has been increasingly supported by recent studies of MAE in various cardiac diseases (Das et al, 2006;Konno et al, 2015;Lu et al, 2017;Sha et al, 2011;Take & Morita, 2012), including HCM (Debonnaire et al, 2015;Konno et al, 2015;Lu et al, 2017). Fibrosis or tissue heterogeneity increases susceptibility to reentry and arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially relevant articles identified from search of MEDLINE (n = 7) and EMBASE database (n = 8) and screened for retrieval Title and abstract review of potentially relevant articles (n = 12) 1 article was excluded at this stage because of abstract presented Exclusion of 3 duplications 11 articles underwent full-length article review 6 articles were excluded at this stage as they were -1 case report -2 no outcome of interest -1 conducted in non-hypertrophic cardiomyopathy -2 review article 5 articles underwent meta-analysis The importance of fQRS, which is suggestive of myocardial scarring and fibrosis, has been increasingly supported by recent studies of MAE in various cardiac diseases (Das et al, 2006;Konno et al, 2015;Lu et al, 2017;Sha et al, 2011;Take & Morita, 2012), including HCM (Debonnaire et al, 2015;Konno et al, 2015;Lu et al, 2017). Fibrosis or tissue heterogeneity increases susceptibility to reentry and arrhythmias.…”
Section: F I G U R E 1 Search Methodology and Selection Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies had shown that the presence of fQRS was found to be predictor for bad outcome. In a study by (Lu et al, [24] they studied the prognostic effect of fQRS in patients with hypertrophic cardiomyopathy (HCM). They have found that the presence of fQRS in this group of patients was associated with an adverse outcome.…”
Section: Discussionmentioning
confidence: 99%